Analisis dan Desain Elemen Struktur Beton Bertulang pada Gedung yang Memiliki Kolom Miring dengan Sistem Rangka Pemikul Momen Biasa (SRPMB) - Simatupang, Angelina Dhini Uli Artha; Bayzoni, Bayzoni; Kusnadi, Andi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
The increasing development of high-rise building construction with unique design in Indonesia today can not be denied. The high-rise buildings must have earthquake resistance because of Indonesia is a country that has the risk of an earthquake. This requires a multi-storey structure designer to be able to design a multi-storey building structure with various conditions and configurations. Based on that problems, a building will be designed with unusual shape by inclining the entire main structural column with a slope angle is 80o. And as a comparison, another building will be designed which uses vertical column. The building plan will be located in Banjarmasin, South Kalimantan, Indonesia.The building plans with inclined and vertical column use reinforced concrete material with Ordinary Moment Resisting Frame (OMRF) as a structural strength system. This system is determined by the location of the building based on Indonesian Earthquake Map 2012. The result of the analysis and design is the building with inclined column has greater internal force compared to a building with vertical column and requires a reinforcement of 70.89% more than the building with vertical column.Keywords: earthquake, inclined column, building, concrete reinforcement, vertical column